Pengaruh Intellectual Capital Terhadap Kinerja Keuangan - Hafifi, Luthfi; Sebrina, Nurzi (Jurnal Nuansa Karya Akuntansi, 2025)
The purpose of this study is to find out how the effect of intellectual capital on financial performance using two models, namely A-VAIC and VAIC models. This research is included in the type of causality research using a quantitative approach. The data in this study were sourced from company annual reports obtained from the website of the Indonesian stock exchange and the website of each company that was sampled. In testing the hypothesis, this study used panel data regression analysis using Eviews software version 12. Based on tests carried out, not all hypotheses of the study are supported by either the VAIC model or the A-VAIC model, the results provide a deeper and new insight on how intellectual capital and each component of intellectual capital (human capital, structural/innovation capital, capital employed) relates to financial performance.